Thinking about the Teaching of Spatial Geometry: Didactic Strategies using GeoGebra Software and Concrete Materials - Bozza, Morgana (Scientia cum Industria, 2016)
Such teaching strategy collaborates to improve the knowledge of Spatial Geometry, trying to end the educational gap related to this subject, and instigating reflections about its importance in the students’ lives since the mathematical concepts are present in our daily lives through shapes, areas and volumes. In order to make a change in the school environment it is important to take the first step with a change in the pedagogical practices, thus contributing to learning processes and helping in the decision of the school subjects and the way they will be discussed in the classroom. Considering learning as a process, and being aware that each student has its own way to learn, classes should be planned considering dynamic and active methodologies, involving the students and allowing them to be protagonists of their own learning while they think about and interact with the object of knowledge, as the mere memorization of formulas is not acceptable anymore. Thus, the following study proposes didactic ways to work some Spatial Geometry concepts, emphasizing the volumes and using technological resources as GeoGebra software and concrete materials. http://dx.doi.org/10.18226/23185279.v3iss3p134